Using an Assessment Tool to Further Tobacco Control Accomplishment in Thailand - Naowarut Charoenca; Nipapun Kungskulniti; Duangkamon Sritabutra; Siriwan Pitayarangsarit; Stephen L Hamann (SAGE Publishing, 2018)
Background: Because implementation of the Framework Convention on Tobacco Control (FCTC), a World Health Organization (WHO) treaty to reduce tobacco use, is an important goal of the 2015 United Nations Sustainable Development Goals (SDGs) and Thailand has sought to fully comply with all its articles, a multiperspective assessment was developed to ensure that any gaps in compliance with FCTC provisions were identified and addressed. Method: One assessment mechanism of this multicomponent assessment was the development by experts and use by stakeholders of a 3-tiered rating of all major provisions of the main articles of the FCTC. The results of the performance ratings on FCTC articles by a diverse group of stakeholders were used to spotlight areas of local and regional implementation and compliance with FCTC provisions. Results: Implementation ratings by stakeholders generally followed the chronology of WHO priorities as reflected in the development by WHO of guidelines for the various FCTC articles with highest ratings for articles 6, 8, 11, 12, 14, 15, and 16. However, only 5 articles (Articles 6, 11, 12, 15, and 16) reached level 2 (effectiveness) of the 3-level rating; articles 6, 8, 11, 13, and 14 are discussed because they are the WHO priority articles of the MPOWER tobacco control policy. Importantly, stakeholders cited problems with lack of completeness of present Thai law and processes for enforcement, as well as lack of public understanding regarding tobacco control strategies and provisions. Conclusions: Overall, the breadth and inclusiveness of the stakeholder approach devised for improving implementation by the Tobacco Control Research and Knowledge Management Center provided greater understanding about shortcomings of present policy and resource management which informed the Tobacco Products Control Act passed in 2017 and plans for advancing stronger Thai regulation by local and national government.